Leverage on small-scale primordial non-Gaussianity through cross-correlations between CMB E-mode and μ-distortion anisotropies. Issue 1 (24th February 2022) - Remazeilles, Mathieu; Ravenni, Andrea; Chluba, Jens
ABSTRACT: Multifield inflation models and non-Bunch–Davies vacuum initial conditions both predict sizeable non-Gaussian primordial perturbations and anisotropic μ-type spectral distortions of the cosmic microwave background (CMB) blackbody. While CMB anisotropies allow us to probe non-Gaussianity at wavenumbers k0.05 Mpc^-1, μ-distortion anisotropies are related to non-Gaussianity of primordial perturbation modes with much larger wavenumbers, k740 Mpc^-1 . Through cross-correlations between CMB and μ-distortion anisotropies, one can therefore shed light on the aforementioned inflation models. We investigate the ability of a future CMB satellite imager like LiteBIRD to measure μ T and μ E cross-power spectra between anisotropic μ-distortions and CMB temperature and E -mode polarization anisotropies in the presence of foregrounds, and derive LiteBIRD forecasts on f_NL^μ (k740 Mpc^-1) . We show that μ E cross-correlations with CMB polarization provide more constraining power on f_NL^μ than μ T cross-correlations in the presence of foregrounds, and the joint combination of μ T and μ E observables adds further leverage to the detection of small-scale primordial non-Gaussianity. For multifield inflation, we find that LiteBIRD would detect f_NL^μ =4500 at 5σ significance after foreground removal, and achieve a minimum error of σ (f_NL^μ =0) 800 at 68 per cent CL by combining CMB temperature and polarization. Due to the huge dynamic range of wavenumbers between CMB and μ-distortion anisotropies, such large f^μ _NL values would still be consistent with current CMB constraints in the case of very mild scale dependence of primordial non-Gaussianity. Anisotropic spectral distortions thus provide a new path, complementary to CMB B -modes, to probe inflation with LiteBIRD .